Raven tales. Child of tears [videorecording (DVD)] (Indigenous Collection., 2017)
In this episode, Qos and Igis are unable to have a child, so Frog (Carmen Moore, Wolf Lake, Godiva's) tells Igis to visit Dzunakwa, an old witch who lives deep in the forest. Dzunakwa agrees to help her, and tells Igis to mix her tears together with a handful of dirt to form the shape of a little boy. Dzunakwa brings him to life, and little Klundux is born! But will the children of the village accept this little child made of tears, and what terrible price shall be paid for Dzunakwa's help?